Transformational Leadership in Strengthening Religious Moderation in Private Islamic Higher Education Institutions in Riau Province - Djeprin E. Hulawa; Kadar M. Yusuf; Alwizar Alwizar; Afriza Afriza; Hakmi Wahyudi; Jon Pamil (SYAMIL: Journal of Islamic Education, 2024)
This research is motivated by several issues related to radicalism and religious violence still prevalent in Indonesia's public and private universities. The survey results by the National Counter Terrorism Agency (BNPT) of Indonesia reported that as many as 39% of students in 15 provinces in Indonesia are indicated of being attracted to radical ideologies and fundamentalist movements. This research aims to describe the pattern of transformational leadership in strengthening religious moderation among students of Private Islamic Higher Education Institutions (PTKIS) in the Riau Province to provide an ideal and humanistic alternative model for the development of religious moderation. This research employs field research methodology, utilizing data collection techniques such as interviews, observations, and documentation to address the research question, "How does transformational leadership contribute to strengthening religious moderation among PTKIS students in Riau?" Based on the research findings, the pattern of transformational leadership applied by the four leaders of PTKIS in Riau positively impacts religious moderation among their respective campus students by carrying out 5 strategic steps included in the discussion.